Coagulation Studies on Separated Fibrinogen Break-down Products - Gormsen, J; Laursen, B (Thrombosis and Haemostasis, 1968)
Fibrinogen break-down products obtained by plasmindigestion in vitro (human material) are separated by column chromatography on DEAE-Sephadex. The various fractions are defined immunologically and by means of disc acrylamide electrophoresis. A plasminsensitive and a plasminresistant fraction exhibiting E- and D-antigenic properties respectively significantly inhibit some early stages of bloodcoagulation, when present in the final concentration of 5–25 mg%. Some other labile intermediates were less active. No significant prolongation of plasma thrombin time is obtained using separated D- or E-fractions even in final concentration of 100 mg%.